Intercultural relations among migrants from Caucasus and Russians in Moscow. (May 2016) - Lebedeva, Nadezhda; Tatarko, Alexander; Berry, John W.
Abstract: This study examines intercultural relations in post-Soviet Russia. Russia currently has the world's second highest number of immigrants with most migrants coming from the former Soviet Union, mainly the Central Asian and South Caucasian states. The research was carried out in Moscow, which is the most attractive destination for these immigrants. The paper presents the findings of an empirical study with migrants ( N  = 378) and residents of Moscow ( N  = 651) examining their intercultural relations, including their acceptance of multicultural ideology, intercultural contacts, intercultural strategies and mutual adaptation. The study was guided by three general hypotheses : the integration, the multicultural and the contact hypotheses. Data processing was carried out using path analysis, separately for migrants and Muscovites. For both samples, multicultural ideology predicts the strategy of integration positively, and of assimilation negatively. Intercultural contacts predict both acculturation strategies positively for migrants, but not for Muscovites. For migrants, both strategies positively predict life satisfaction, and integration predicts better sociocultural adaptation. For Muscovites, integration predicts life satisfaction. These specific findings fully support the two underlying hypotheses: integration and multicultural for both groups and contact hypothesis only for migrants. Multicultural ideology has positive relation to intercultural contacts of Muscovites and has indirect positive impact on intercultural strategies of migrants. Models demonstrated similar as well as different psychological processes underlying mutual acculturation and intercultural relations in the two groups. The similarities suggest that efforts should be directed at developing a multicultural ideology and facilitating intercultural contacts between migrants and members of the larger society.